Justice and penal reform: re-shaping the penal landscape - Farrall, Stephen; Goldson, Barry; Loader, Ian; Dockley, Anita (Routledge, 2016)
1. From bad to worse : crime, incarceration, and the self-wounding of society / Jonathan Jacobs -- 2. Punishment, suffereing and justice / Matt Matravers -- 3. Punishment, legitimacy and the role of the state : reimagining more moderate penal policies / Sonja Snacken -- 4. What good is punishment? / Fergus McNeill -- 5. Civic repair and penal reform : the role of the state in rebuilding trust / Vanessa Barker -- 6. Crime, justice and 'the man question' / Ann Oakley -- 7. Rights, justice and single-mindedness / Therese Murphy and Noel Whitty -- 8. Examining imprisonment through a social justice lens / Ruth Armstrong and Shadd Maruna -- 9. Democracy (re)imagined : some proposals for democratic policing / Elizabeth Turner -- 10. Participatory innovation in criminal justice : why, how, and how far? / Albert W. Dzur.